Pengaruh Brand Image, Service Quality, Dan Brand Trust Terhadap Keputusan Penggunaan (Studi Pada Jasa Gudang Online Crewdible di Malang) - Syahrul Zahroni; Agus Widarko; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
AbstrackThe purpose of this study is to explain brand image, service quality, brand trust, and usage decisions and to find out how to explain brand image, service quality, and brand trust on partial or simultaneous usage decisions. This research method uses quantitative methods and this type of research is simple random sampling. The sample of this research is 58 Crewdible online warehouse partners located in Sukun, Malang city. To obtain accurate and detailed data, this study used a questionnare data collection method. The data analysis usd in instrument test, normality test, classical assumption, multiple linier regression analysisi, hypothesis test, and coefficient of determination using SPSS 25 for Windows. The result of this study indicate that brand image, service quality, brand trust simultaneously influence the decision to use Crewdible online warehouse services in Malang. While partially, brand image does not affect the decision to use, service quality does not affect the decision to use, and brand trust does not affect the decision to use the Crewdible online warehouse service in Malang. Keywords : Brand Image, Service Quality, Brand Trust, and Usage Decision.